Clinical-anthropometric characteristics of COPD outpatients belonging to the different groups and having different severity of airway obstruction. - K. Y. Gashynova (Medičnì Perspektivi)
The aim of the study was to compare the clinical and anthropometric characteristics of patients with COPD, which differ in the degree of airways obstruction and belong to groups A, B, C, D in accordance with GOLD, 2011 classification. A total of 112 ambulatory COPD patients in remission made the study sample. Anthropometric data, body mass index, medical history, dyspnea by mMRC scale, and spirometry was performed for all patients. There was confirmed that outpatients with COPD is a heterogeneous group, in which the majority are those with moderate (48.22 %) and severe (30.36 %), airway obstruction. Despite the vast majority of men among outpatients, the percentage of women among patients with mild to moderate obstruction (22.58±5.31 %) was significantly higher (p=0.002) as compared with those with severe or very severe limitation of airflow (6.00±3.36 %). Patients with severe and very severe obstruction were of significantly older age (p = 0.024). At the same time, the distribution of patients according to the GOLD, 2011 classification, demonstrate that all groups did not differ on any of the anthropometric indicators, including gender and age (p > 0.050). Distribution of patients by groups with different risk for future exacerbations is not a mirror image of gradation in accordance with the degree of airway obstruction. Every second (50.00±4.43 % of cases) patient is included in group C and every tenth (10.20±4.32 %) belongs to the group D not due to degree of bronchial obstruction, but due to the number of exacerbations in the past year. Therefore, in future studies it is advisable to use both principles of patients’ classification.